PERLINDUNGAN HUKUM ABK INDONESIA DI KAPAL ASING DALAM PERSPEKTIF HUKUM NASIONAL - Daniel Surianto; Ida Kurnia (Jurnal Hukum Adigama, 2021)
Introduction: Indonesian crew members are every Indonesian citizen who will be, are currently or have been doing work by receiving wages on a foreign ship. In its development, there have been many cases of Indonesian ship crew working on foreign ships such as violence, torture, unpaid wages and so on. This study aims to determine the role of the government in providing legal protection against cases experienced by the crew of Indonesian ships when they are, are or have worked on foreign ships in the perspective of national law. Methods: Normative juridical research uses a normative juridical approach based on primary and secondary legal materials. Result: The data shows that there are a number of complaints and cases of Indonesian Ship Crew members working on foreign ships. Conclusion: This research shows that the regulations in the form of laws and regulations and the policies of the Indonesian government in providing protection are good, but it is still necessary to form policies and regulations that do not overlap, there is a lack of cooperation between related ministries / institutions in overcoming trafficking in persons against citizens Indonesia, the lack of oversight from law enforcement officials in terms of recruitment to reviewing the places where ship crew companies work, and the lack of data on the number of Indonesian crew members working on foreign ships.